Ablation of interferon regulatory factor 4 in T cells induces "memory" of transplant tolerance that is irreversible by immune checkpoint blockade. Issue 3 (25th December 2018) - Zhang, Hedong; Wu, Jie; Zou, Dawei; Xiao, Xiang; Yan, Hui; Li, Xian C.; Chen, Wenhao
Abstract : Achieving transplant tolerance remains the ultimate goal in the field of organ transplantation. We demonstrated previously that ablation of the transcription factor interferon regulatory factor 4 (IRF4) in T cells induced heart transplant acceptance by driving allogeneic CD4 + T cell dysfunction. Herein, we showed that heart‐transplanted mice with T cell‐specific IRF4 deletion were tolerant to donor‐specific antigens and accepted the subsequently transplanted donor‐type but not third‐party skin allografts. Moreover, despite the rejection of the primary heart grafts in T cell‐specific Irf4 knockout mice under immune checkpoint blockade, the establishment of donor‐specific tolerance in these mice was unhindered. By tracking alloantigen‐specific CD4 + T cells in vivo, we revealed that checkpoint blockade restored the expression levels of the majority of wild‐type T cell‐expressed genes in Irf4 ‐deficient T cells on day 6 post‐heart grafting, indicating the initial reinvigoration of Irf4 ‐deficient T cells. Nevertheless, checkpoint blockade did not restore cell frequency, effector memory cell generation, and IFN‐γ/TNF‐α production of Irf4 −/− alloreactive T cells at day 30 post‐heart grafting. Hence, targeting IRF4 represents a potential therapeutic strategy for driving intrinsic T cell dysfunction and achieving alloantigen‐specific transplant tolerance. Abstract : Interferon regulatory factor 4 governs allogeneic T cell responses in heart graft recipient mice, and its absence leads to transplant tolerance that is irreversible by immune checkpoint blockade.